1993
DOI: 10.1128/aac.37.4.692
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of granulocyte colony-stimulating factor and RU-40555 in combination with clarithromycin against Mycobacterium avium complex infection in C57BL/6 mice

Abstract: We compared the activities of two different biological-response modifiers with that of clarithromycin against Mycobacterium avium complex infection in C57BL/6 mice. Mice were pretreated daily with clarithromycin (50 mg/kg of body weight subcutaneously [s.c.]), RU-40555 (100 mg/kg s.c.), or granulocyte colony-stimulating factor (G-CSF) at low dose (15 micrograms/kg intraperitoneally [i.p.]) or high dose (300 micrograms/kg i.p.) 3 days before intravenous challenge with 2.5 x 10(7) CFU of the MO-1 strain of M. av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Thus, our data do not support previous observations by other groups. Lazard et al [20] invoked a beneficial effect of G-CSF as adjunct therapy in their chemotherapy studies in BALB/c mice infected with a non-virulent strain of M. avium. We should note, however, that we find that such effects in their work were extremely minor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our data do not support previous observations by other groups. Lazard et al [20] invoked a beneficial effect of G-CSF as adjunct therapy in their chemotherapy studies in BALB/c mice infected with a non-virulent strain of M. avium. We should note, however, that we find that such effects in their work were extremely minor.…”
Section: Discussionmentioning
confidence: 99%
“…Newman et al [19] have shown that neutrophils from AIDS patients significantly inhibited M. avium growth after administration of rHuG-CSF ex vivo. Using a mouse model, Lazard et al [20] have shown that G-CSF in combination with clarithromycin was more effective than clarithromycin alone against M. avium infections. Also, Bermudez and colleagues [21] showed recently an equally beneficial effect of G-CSF on its own on M. avium infections in mice.…”
Section: Disseminated Infection By Mycobacterium Avium Complex (Mac)mentioning
confidence: 99%
“…The MO-1 strain of MAC, used in our previous studies (2,(8)(9)(10)(11)(12), was isolated from a patient with AIDS and used after a single subculture on mycobacterial Middlebrook 7H11 agar (Difco Laboratories, Detroit, Mich.) supplemented with Middlebrook OADC enrichment (Difco). One flat transparent colony was picked and cultivated at 37ЊC in Middlebrook 7H9 broth (Difco) supplemented with ADC enrichment (Difco) in Falcon tissue culture flasks (Becton Dickinson, Oxnard, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial load reaches concentrations higher than 10 8 CFU/g of spleen and higher than 10 7 CFU/g of lung after 6 months of infection, without the spontaneous clearance of bacteria observed with Swiss Webster mice (4-6). The model of early infection of normal C57BL/6 mice may be used for a rapid screening of drugs (8,9,10). In patients with AIDS, MAC infection has a subacute or a chronic clinical course.…”
mentioning
confidence: 99%
“…Numerous studies have been performed either in vitro (25,28,36,49) or on macrophages (46) and in animal models (6,21,34,38,39) with classic or more recent antituberculous agents (ciprofloxacin, sparfloxacin, azithromycin, and clarithromycin) alone or in combi-…”
mentioning
confidence: 99%